CATEGORIES OF STUDENTS WITH DISABILITIES (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
This article discusses the different categories of students with disabilities, focusing on their educational needs and the importance of inclusive education. It highlights various teaching methods and support systems that help ensure equal opportunities for students with special needs.